(untitled) (Veterinary Science, 2021)
The objective of the present work was to compare the values of the percentages of the different fractions in the milk casein of Criollo and Saanen goats. For this purpose, 6 adult goats of each breed from a commercial goat herd, located in the semi-arid region of central western Argentina, were evaluated. The goats were fed on alfalfa and corn grain, and service was performed by natural mating. Samples were collected by hand milking, taking 100 c.c./animal at 15, 30 and 45 days post-partum. To determine the percentage of alpha, beta and kappa casein, the UREA-PAGE vertical gel electrophoresis method was used and the bands were read applying the semi-quantification method with ImageJ software. The results found showed that in both breeds the values of alpha casein were increasing, while those of beta and kappa casein decreased throughout the sampling. Likewise, it was found that alpha casein was higher in Saanen goat milk, while the percentages of beta and kappa casein were higher in Criollo goat milk, finding a significant statistical difference for alpha and beta casein at the three times evaluated and in the case of kappa casein only in the 45-day sampling. It was concluded that Criollo goat milk has a lower percentage of alpha casein than Saanen goat milk, which would make it less allergenic and has a higher percentage of beta and kappa casein, a situation that would allow a quick coagulation for cheese production. and a higher stability and firmness in yogurts.